2009
DOI: 10.1016/j.tetlet.2008.12.010
|View full text |Cite
|
Sign up to set email alerts
|

A microwave-assisted stereoselective synthesis of polyandrocarpamines A and B

Abstract: A stereoselective synthesis of the marine natural products, polyandrocarpamines A and B, has been achieved using a high-yielding one-step aldol condensation reaction under microwave conditions. The structures of both synthetic compounds were confirmed following 1D and 2D NMR, UV, IR and MS spectral analysis, and by comparison with literature data. Both synthetic natural products were assigned Z geometry about their exocyclic double bond on the basis of 13 C/ 1 H long-range coupling constants, which were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
0
24
1
Order By: Relevance
“…793 Botryllazine B (Botryllus leachi) 794 and analogues are mixed-type inhibitors of recombinant human aldose reductase. 797 The structures of eudistomins Y 1 -Y 6 (Eudistoma sp.) 797 The structures of eudistomins Y 1 -Y 6 (Eudistoma sp.)…”
Section: View Onlinementioning
confidence: 99%
“…793 Botryllazine B (Botryllus leachi) 794 and analogues are mixed-type inhibitors of recombinant human aldose reductase. 797 The structures of eudistomins Y 1 -Y 6 (Eudistoma sp.) 797 The structures of eudistomins Y 1 -Y 6 (Eudistoma sp.)…”
Section: View Onlinementioning
confidence: 99%
“…The intermediate 4 was reacted with other commercially available material 4-hydroxybenzaldehyde 5a or vanillin 5b to form 6a or 6b by condensation according to the literature. 6,8) Compounds 6a, b was oxidized by tert-butylhydroperoxide (TBHP) to obtain the important intermediate 7a, b. Then corresponding amine, alkane amines or alcohol amines were introduced onto the sulfonic group of compounds 7a, b to obtain the targeted compounds 1a-k, 2a-k.…”
Section: Resultsmentioning
confidence: 99%
“…1) Resourceful novel and structurally diverse metabolites from marine organisms, in particular those coming from sponges, have proved to display a wide variety of biological activities including antihistamine activity, 2) antiinflammation, 3) neuroprotective activity, 4,5) antitumor, 6) antioxidant, 7) etc. For example (see Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These simple alkaloids were first isolated and synthesized in 2002, and although sufficient quantities were generated by total synthesis, no biological activity has been reported so far. Davis et al[45] reported an MWassisted synthesis of polyandrocarpamine A (201) and B (202). They started from the HCl salt of glycocyamidine (203), which was condensed with aldehyde 204 in an NaOAc-AcOH slurry under MW irradiation at 160 • C for 30 min to yield the polyandrocarpamines A (201) (56%) and B (202) (80%) in high yields (Scheme 19.43).…”
mentioning
confidence: 99%